Theory of Electrostatically Regulated Binding of T4 Gene 32 Protein to Single- and Double-Stranded DNA - Rouzina, Ioulia (Biophysical Society, 2005)
Bacteriophage T4 gene 32 protein (gp32) is a single-stranded DNA binding protein, which is essential for DNA replication, recombination, and repair. In a recent article, we described a new method using single DNA molecule stretching measurements to determine the noncooperative association constants K(ds) to double-stranded DNA for gp32 and *I, a truncated form of gp32. In addition, we developed a single molecule method for measuring K(ss), the association constant of these proteins to single-stranded DNA. We found that in low salt both K(ds) and K(ss) have a very weak salt dependence for gp32, whereas for *I the salt dependence remains strong. In this article we propose a model that explains the salt dependence of gp32 and *I binding to single-stranded nucleic acids. The main feature of this model is the strongly salt-dependent removal of the C-terminal domain of gp32 from its nucleic acid binding site that is in pre-equilibrium to protein binding to both double-stranded and single-stranded nucleic acid. We hypothesize that unbinding of the C-terminal domain is associated with counterion condensation of sodium ions onto this part of gp32, which compensates for sodium ion release from the nucleic acid upon its binding to the protein. This results in the salt-independence of gp32 binding to DNA in low salt. The predictions of our model quantitatively describe the large body of thermodynamic and kinetic data from bulk and single molecule experiments on gp32 and *I binding to single-stranded nucleic acids.